High-performance Ni-based superalloy 718 fabricated via arc plasma directed energy deposition - Farias, Francisco Werley Cipriano (2024)
Funding Information: The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210986 EC. This activity has received funding from the European Institute of Innovation and Technology (EIT) Raw Materials through the project Smart WAAM: Microstructural Engineering and Integrated Non-Destructive Testing. YZ acknowledges the National Natural Science Foundation of China (51601091), the Natural Science Foundation of Jiangsu Province (BK 20160826), the Six Talent Peaks Project of Jiangsu Province (2017-XCL-051), the Fundamental Research Funds for the Central Universities (30917011106), and Key Research and Development Plan of Jiangsu Province (BE2020085). Institut Pprime gratefully acknowledges “Contrat de Plan Etat - Région Nouvelle-Aquitaine (CPER)” as well as the “Fonds Européen de Développement Régional (FEDER)” for their financial support to part of the reported work. Publisher Copyright: © 2024 The Authors